A Phase I Study of Apolizumab, an Anti-HLA-DR ß-chain Monoclonal Antibody, in Patients With Solid Tumor Malignancies. (1st July 2022) - Fracasso, Paula M.; Goodner, Sherry A.; Wildi, Jonathan D.; Naughton, Michael J.; Linette, Gerald P.; Govindan, Ramaswamy; Tan, Benjamin R.; Blum, Kristie A.; Jones, Gary J.; Pearce, Tillman E.; Levitt, Daniel J.; Clamon, Gerald H.
Abstract : Background: Human leukocyte antigen (HLA)-DR, a member of the major histocompatibility complex class II antigen family, is a target for antibody-based therapeutics. Apolizumab (Hu1D10, Remitogen), a humanized IgG1 monoclonal anti-HLA-DR ß-chain antibody targets the antigen, 1D10, expressed on a wide variety of hematologic and solid tumor malignancies. In this Phase 1 trial, the maximum tolerated dose and dose-limiting toxicity of weekly apolizumab in patients with advanced solid tumor malignancies were determined. Patients and Methods: Eligible patients with refractory solid tumors were initially screened for ID10 Ag on their tumor. Patients whose tumors expressed 1D10 were administered apolizumab 0.5, 1.0, 1.5, or 3.0 mg/kg intravenously over 90 minutes weekly for 4 consecutive weeks, followed by a 4-week break, and assessment of response. Patients whose disease had not progressed were offered additional treatment. Results: Tumors from 75 patients were screened for 1D10 Ag of which 17 patients were positive and underwent treatment. The first 3 dose levels were well-tolerated. Dose-limiting toxicities of grade 3 infusion-related hypersensitivity reactions and grade 3 headache and hypertension occurred in 2 patients, respectively, at apolizumab 3.0 mg/kg. Four patients, 1 each with breast carcinoma, melanoma, renal cell carcinoma, and sarcoma had stable disease for a median of 15 weeks (range: 12 to 19 wk). Conclusion: Apolizumab can be administered safely at a maximum tolerated dose of 1.5 mg/kg for 4 consecutive weeks. Adverse events and limited clinical data in both hematologic and solid tumor malignancies resulted in discontinuation of clinical development of apolizumab. HLA-DR remains an interesting immunotherapeutic target.